Activity of Cytotoxic Flavanoids against a P-388 Murine Leukemia Cell Line from the Stem Bark of Aglaia elliptica (Meliaceae) - Hidayat, Ace Tatang; Farabi, Kindi; Harneti, Desi; Maharani, Rani; Nurlelasari,; Supratman, Unang; Shiono, Yoshihito (UI Scholars Hub, 2017)
Two mixtures of flavanoid compounds (1 and 2), a mixture of catechin (1a) and epicatechin (1b), and a mixture of gallocatechin (2a) and epigallocatechin (2b), were isolated from the active fraction of the stem bark of Aglaia elliptica methanol extract. The chemical structure of the compounds was identified with spectroscopic data, including UV, IR, NMR (1H, 13C, DEPT 135°, HMQC, HMBC, 1H-1H COSY), and MS, and additionally compared with previously reported spectral data. All compounds were evaluated for their cytotoxic effects against P-388 murine leukemia cells. Compound 2 showed cytotoxicity against the P-388 murine leukemia cell, with an IC50 value of 7.79 µg/mL, but compound 1 was found not to be active (more than 100 µg/mL).